The Internet Initiative at the Atlanta Fulton Public Library - Agnew, Grace B. (DESIDOC Journal of Library & Information Technology, 2002)
This article presents the efforts of Atlanta-Fulton Public Library in providing internet access and database search services to information seekers encompassing homes, schools and offices. Two main features of this internet initiative described are: Adult learning service and internet access to high schools. http://dx.doi.org/10.14429/dbit.16.1.3245